2007
DOI: 10.1136/ard.2006.066001
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular outcomes in high risk patients with osteoarthritis treated with ibuprofen, naproxen or lumiracoxib

Abstract: These data suggest that ibuprofen may confer an increased risk of thrombotic and CHF events relative to lumiracoxib among aspirin users at high cardiovascular risk. The study indicates that naproxen may be associated with lower risk relative to lumiracoxib among non-aspirin users. This study is subject to inherent limitations, and therefore should be interpreted as a hypothesis-generating study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(68 citation statements)
references
References 35 publications
0
63
0
5
Order By: Relevance
“…Ibuprofen, a nonsteroidal anti-inflammatory drug, has been widely used to treat pain, fever and inflammation due to its lower incidence of digestive [19,20] and renal adverseness [20,21,22] and cardiovascular risk [23,24] than most nonsteroidal anti-inflammatory drugs. It is a major medicine in the Essential Drugs List of the World Health Organization and available over the counter in most areas.…”
Section: Discussionmentioning
confidence: 99%
“…Ibuprofen, a nonsteroidal anti-inflammatory drug, has been widely used to treat pain, fever and inflammation due to its lower incidence of digestive [19,20] and renal adverseness [20,21,22] and cardiovascular risk [23,24] than most nonsteroidal anti-inflammatory drugs. It is a major medicine in the Essential Drugs List of the World Health Organization and available over the counter in most areas.…”
Section: Discussionmentioning
confidence: 99%
“…However, cyclooxygenase (COX)-2-specific drugs might be beneficial for adverse effects on cartilage. Recently observations have suggested that COX-2-specific drugs used at present also have their side effects and might increase the risk of cardiovascular diseases (20,21). Therefore, we need to develop novel drugs with which treatment for (osteo)arthritis is satisfactory for prolonged treatment of joint disease, including improvement of cartilage and inhibition of inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…A number of drugs have been designed and applied depending on the affected organ, the status of the disease and the characteristics of the involved patient; however, the therapy can be expensive, and its effect may be symptomatic, non-permanent, and could cause collateral damage. For example, non-steroidal anti-inflammatory drugs can have adverse effects on bone tissue by modulating the proliferation, differentiation, adhesion, and migration of osteoblasts (Garcia-Martinez et al, 2015); some of the mentioned drugs, as well as aspirin, have been associated with upper gastrointestinal tract injury, including bleeding and ulcers (Goldstein, 2004;Goldstein and Crier, 2015), and they confer an increased risk for thrombotic and congestive heart failure (Farkouh et al, 2007). Furthermore, another risk factor to be considered is the concurrent use of anti-inflammatory drugs with other medications such as anticoagulants, corticosteroids, serotonin reuptake inhibitors or antihypertensive agents (Goldstein and Cryer, 2015;Kalafutova et al, 2014).…”
Section: Introductionmentioning
confidence: 99%